Odpowiedzi

Najlepsza Odpowiedź!
2009-12-18T13:12:25+01:00
Zadanie 1

a)(3x-1)/2-(x+4)/3=(5x-11)/4 mnożymy przez 12

12*(3x-1)/2-12(x+4)/3 =12(5x-11)/4

6(3x-1)-4(x+4)=3(5x-11)
18x-6-4x-16=15x-33
14x-20=15x-33
14x-15x=-33+20
-x=-13/(:-1)
x=13

b)(pierw.3-x)(pierw3+1)<4-(pierw3-x)^2
3+pierw3-pierw3x-x<4-(3-2pierw3X+x^2)
3-x<4-3+2pierw3x-x^2
x^2-x-2pierw3+2<0
delta= (1-2pierw3)^2-8
delta=1-4pierw3+12-8=-4pierw3+5
pierw z delty=pierw(-4pierw3+5)
x=(1-2pierw3)-(-4pierw3+5))/2=-4+2pierw3/2=pierw3-2
x=(4+6pierw3)/2=3pierw3+2
rozwiązanie : xnależy do zbioru (pierw3-2,3pierw3+2)

c)x^2-4pierw2+8=0
delta= 32-32=0
x=-4pierw2/2=-2pierw2

d)3x^2>/8/:3
x^2>/8/3
x>/2pierw2/pierw3= 2pierw6/3

e)2x^4-8x^3+3x^2-12x=0
2x^3(x-4)+3x(x-4)=0
(x-4)(2x^3+3x)=0
(x-4)x(2x^2+3)=0
x=4, x=0

f)1/9x^6+x^5=1/3x^5-x^4
1/9x^6+2/3x^5+x^4=0
x^4(1/9x^2+2/3x+1)=0
delta=4/9-4/9
delta=0
x= -2/3/2/9=-1/3
rozwiązanie x=0 i x=-1/3

Uwaga ^-oznacza potęgę a /-ułamek

zadanie 2
{3x-6+2y-2=y-7
{2x+2+3y-3=2y+2

{3x+y-1=0
{2x+y-3=0

{y=1-3x
{2x+1-3x-3=0
-x-2=0
-x=2
x=-2
y=1+6=7